(untitled) (The Review of Diabetic Studies, 2024)
Professional organizations and standards, regulations, and recommendations shape nursing practice globally. Education, nursing procedures, collegiality, ethics, teamwork, research, quality, quality of practice, professional practice assessments, resource use, leadership, and communication all have an impact on the duties of registered nurses. Although the RN scope of practice is defined differently by these worldwide nursing practice ideas, the professional nurse’s role is universally supported. Since 1992, the Saudi Commission for Health Specialists (SCFHS) has governed the classification and registration of nurses. For foreign certified nurses, their guidelines center on credentials, years of practice, hours of continuous education, and international registration. This present study evaluates the scenario in the light of primary data collected from various sources and thereafter interpreting the same using SPSS ver. 22.0.